A study on causes of chronic kidney disease in patients without diabetes mellitus and systemic hypertension in a tertiary care hospital - J., Praveen; A., Tumbanatham; M., Sivashankar (International Journal of Advances in Medicine, 2022)
Background: Chronic kidney disease is an increasing health problem worldwide Thus apart from the well-established risk factors for CKD such as diabetes and systemic hypertension, the possibility that environmental, demographic, and various other risk factors an influence in developing chronic kidney disease has been assessed in several studies. Hence, the present study aimed to study the clinical and laboratory profile of chronic kidney disease in non-diabetic and non-hypertensive patients Methods: The study was enrolled 100 patients diagnosed with chronic kidney disease without diabetes and systemic hypertension in the department of general medicine and department of nephrology in a tertiary care hospital, Pondicherry for 1 year. The baseline data such as socioeconomic status, history of self-consumption of natural medicine and NSAIDs, their occupations, location of their living place, and routine laboratory parameters were collected and analysed. Results: The socioeconomic status of the present study revealed that upper lower class was the predominant status and the majority of the patients were housewives and farmers. 38% of the patients were exposed to insecticides that were associated with CKD (p=0.0327). 40% of the study population was victims of NSAID consumers (p=0.0236). 42% was consumed natural medication on their own for their illness 46 without any consultation (p=0.0324). The patients came from Cuddalore predominantly (22%). Conclusions: Insecticide exposure, self-consumption of NSAIDs, and natural medicine are the main causes that progress to CKD in the present study.